Preliminary Microstructure and Hardness Studies of A356/Stainless Steel Composite via Gravity Die Casting Technique - Mazlee Mohd Noor (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.